A systematic review of teachers’ digital competence and its effect on students’ academic self-efficacy, learning engagement and other outcomes - Ruizhu Luo; Hazrati Binti Husnin; Mohammad Hafiz Bin Zaini (Environment and Social Psychology, 2025)
This systematic review synthesizes 25 empirical studies (1/1/2015–16/6/2025) to examine the impact of teachers’ digital competence on students’ academic self-efficacy, learning engagement, and other related outcomes. The findings reveal that teachers’ digital competence boosts academic self-efficacy by fostering confidence and self-regulation. It also enhances learning engagement across behavioral, emotional, and cognitive dimensions. These effects are supported by frameworks such as TPACK and Social Cognitive Theory. Quantitative research and questionnaires were the most commonly used methods, and technology integration environments (e.g., AR/VR, AI tools) in improving students’ other related outcomes were the most frequent variable focus. However, the existing research exhibits geographical biases (with a predominance of studies from developed regions), methodological limitations (including an overreliance on cross-sectional surveys), and a focus on higher education, which leaves K-12 and vocational contexts underexplored. Key gaps include inconsistent measurement tools and insufficient examination of mediating mechanisms (e.g., the role of academic self-efficacy in the relationship between teachers’ digital competence and learning engagement). This review underscores the need for longitudinal studies, standardized assessments, and more equitable research representation in economically underdeveloped regions. Practical implications highlight the importance of integrating technical and pedagogical training in teacher development programs to optimize digital learning environments.